Sri Lanka, what went wrong? : J.R. Jayewardene's free & righteous society - Vittachi, V. P. (New Delhi : Navrang Booksellers and Publishers, 1995)
Chiefly relates to the political conditions prevailing in Sri Lanka during Junius Richard Jayewardene's rule as president.
Includes index.
Keywords: Sri Lanka -- Politics and government -- 1978-; 62-12